Implementación de un aplicativo móvil que permita gestionar la información y la toma de decisiones en el departamento de vinculación en la Universidad Técnica de Cotopaxi Extensión La Maná - Marcillo Tonato, Jefferson Andrés (2021)
At the Technical University of Cotopaxi in La Maná, there are Community Engagement Projects and Pre-Professional Internships where teachers and students participate and must document all of the activities, they perform through monthly reports that are made mainly through generic tools which do not allow an efficient management of information in the Department of Community Engagement. This proposal is related to the development of an information system that contributes to the automation of the processes necessary for a student to be able to approve their participation in Community Engagement Projects and Pre-Professional Internships as a requirement to obtain their third level degree. The first chapter presents a bibliographic review of contents that serve as a reference to develop this proposal, in the second chapter different research instruments and technical formats are designed to develop the system using the agile Scrum methodology. Finally, the third chapter includes the results of the research from a scientific point of view, presenting the diagnosis and giving solution to the evidenced problem, as part of the development and validation process through the method of expert judgment, fulfilling the implementation of a functional system, which delivers percentage results through a mathematical and statistical calculation obtained from the information generated by the students, thus becoming a necessary tool for the decision making by teachers, tutors and authorities.